Evaluation of immunoassays for the diagnosis of Schistosoma japonicum infection using archived sera. - Jing Xu; Rosanna W Peeling; Jia-Xu Chen; Xiao-Hua Wu; Zhong-Dao Wu; Shi-Ping Wang; Ting Feng; Shao-Hong Chen; Hao Li; Jia-Gang Guo; Xiao-Nong Zhou (PLoS Neglected Tropical Diseases)
Background With a national program initiated recently to reduce transmission of Schistosoma japonicum in the People's Republic of China (P.R. China), there is an urgent need for accessible, quality-assured diagnostics for case detection, surveillance, and program monitoring of chemotherapy efficacy and other control interventions in areas of low endemicity. We compared the performance of nine immunodiagnostic tests developed in P.R. China for detection of antibodies against S. japonicum and established their priority for further assessment in field settings. Methodology/principal findings Using the Kato-Katz technique as the reference standard, 240 well-characterized archived serum specimens (100 positive and 140 negative) were evaluated in nine immunological tests developed in P.R. China. The enzyme-linked immunoelectrotransfer blot assay (EITB), which uses an adult worm extract of S. japonicum, supplied by the Center of Disease Control and Prevention, USA, was also evaluated. The sensitivity and specificity of each test were determined and the reproducibility of each test was assessed by evaluating operator-to-operator and run-to-run variation. In addition the simplicity of use for the end-user was evaluated. All tests showed good sensitivities ranging from 92.0% (95% confidence interval (CI): 86.7-97.3%) to 98.0% (95% CI: 95.3-100.0%). The test specificities varied from 70.0% (95% CI: 62.4-77.6%) to 97.1% (95% CI: 94.4-99.9%). All tests showed excellent reproducibility with a discordant rate in the range of 0-10.0% for operator-to-operator variation and run-to-run variation. All tests, except one magnetic particle-based enzyme-linked immunosorbent assay, were found to be easy to use, especially the dot immunogold filtration assays. Conclusions/significance Most evaluated tests had acceptable performance characteristics and could make an impact on the schistosomiasis control programs in P.R. China. Three tests with the highest sensitivity, specificity and greatest ease of use, were selected for further evaluation in field settings.